PENERAPAN PERMAINAN KECIL UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA DALAM PEMBELAJARAN PENJASORKES (STUDI PADA SISWA TUNA NETRA TOTAL BLIND SDLBN LAMONGAN) - DIDA FIRMAN, RIO (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract Education as a process of coaching and developing student that lasts a lifetime and is organized with an ex-ample, a willingness to build and develop creativity in the learning process. Education has a pedagogical objective, therefore less education complete without penjasorkes, because penjasorkes as the basis for physical activity for people to understand the world and himself that naturally develops in line with the changing times. For that to penjasorkes learning process will run smoothly and be able to bring motivation and feelings of pleasure and delight of the students to participate in learning, teachers should be good to develop a variety of simple game in accordance with the characteristics of the students in the form of a sports game. Of the learning process that was developed is also expected to change behavior that is reflected by the increasing student motivation. To determine the characteristics of the growth and development of students, teachers should prepare a method which should reflect the characteristics of adaptive penjas itself. Small game is one attempt to do by teachers for learning can be fun. The purpose of this study was to determine the effect of the application of simple game to improve students' motivation in penjasorkes learning. The population in this study were total blind students SDLBN Lamongan. From this research we can conclude that there is a significant effect of the application of small game to improve students' motivation in learning adaptive penjas as evidenced from the results of the t test 13,856 count > t table value of 2.920 with a significance level of 0.05. Magnitude of the influence of small game at enhancing motivation student learning in adaptive learning penjas amounted to 8.73%. Keywords: Small game, Motivation study